2018
DOI: 10.1182/blood-2017-09-806489
|View full text |Cite
|
Sign up to set email alerts
|

A landscape of germ line mutations in a cohort of inherited bone marrow failure patients

Abstract: Bone marrow (BM) failure (BMF) in children and young adults is often suspected to be inherited, but in many cases diagnosis remains uncertain. We studied a cohort of 179 patients (from 173 families) with BMF of suspected inherited origin but unresolved diagnosis after medical evaluation and Fanconi anemia exclusion. All patients had cytopenias, and 12.0% presented ≥5% BM blast cells. Median age at genetic evaluation was 11 years; 20.7% of patients were aged ≤2 years and 36.9% were ≥18 years. We analyzed genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
300
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 265 publications
(321 citation statements)
references
References 43 publications
6
300
0
9
Order By: Relevance
“…On the basis of the phenotypic data from the patients in this and recent reports, 6,9,20,36,37 we conclude that heterozygous MECOM mutations or haploinsufficiency of MECOM resulting from microdeletions cause a syndromic disease with a variable phenotypic pattern, varying from severe BMF with multiple organ manifestations to isolated RUS without additional manifestations. Although RUS and BMF are the most common manifestations, none of these symptoms are mandatory for diagnosis of a MECOM-associated syndrome.…”
Section: Nasupporting
confidence: 59%
See 4 more Smart Citations
“…On the basis of the phenotypic data from the patients in this and recent reports, 6,9,20,36,37 we conclude that heterozygous MECOM mutations or haploinsufficiency of MECOM resulting from microdeletions cause a syndromic disease with a variable phenotypic pattern, varying from severe BMF with multiple organ manifestations to isolated RUS without additional manifestations. Although RUS and BMF are the most common manifestations, none of these symptoms are mandatory for diagnosis of a MECOM-associated syndrome.…”
Section: Nasupporting
confidence: 59%
“…7,8 A study investigating germ line mutations in a group of 179 patients with IBMFS identified 6 more patients with MECOM mutations; interestingly, only 1 of them had RUS (supplemental Table 1). 9 In this study, we report on 12 patients with yet unclassified AT from different families caused by mutations in MECOM. We found a continuous spectrum of clinical manifestations in the patients and affected relatives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations